Covid‐19 dermatoses: Acral vesicular pattern evolving into bullous pemphigoid - P.K.C. Goon; O. Bello; L.A. Adamczyk; J.Y.H. Chan; H. Sudhoff; C.C. Banfield (Wiley, 2021)
Abstract Bullous pemphigoid (BP) appears to be rising in incidence across the Western World, especially in the elderly. Some of the pathogenetic mechanisms involving antigen mimicry and antibody cross‐reactivity have been elucidated for cases associated with neurological disease and certain drugs. There have been reports of cutaneous manifestations of Covid‐19 (SARS‐Cov2 infection) as the pandemic has raged across the world. We report here a case of prolonged Covid‐19, symptomatic with dermatoses only, which was seen to evolve initially from a maculo‐papular exanthema with acral vesicular dermatitis, into classical BP disease. This was confirmed histologically by positive skin autoantibody serology, direct IMF on peri‐lesional skin and also salt‐split IMF. Although possible that the development of BP could be a purely co‐incidental finding during Covid‐19, we suggest that it is more likely that prolonged SARS‐Cov2 infection triggered an autoimmune response to the basement membrane antigens, BP 180 and 230. To our knowledge, this is the first case of BP developing during concurrent Covid‐19 disease. It will be necessary to continue dermatological surveillance as the pandemic continues, to collate data on BP incidence and to test these patients for Covid‐19 disease. As the pandemic continues, even potential and rare associations such as this will be clarified eventually. What's already known about this topic? Covid‐19 disease has been associated with a spectrum of dermatoses Common presentations in up to 20% of patients include exanthema, pseudo‐chilblain like acral lesions 'Covid toes', livedo‐/retiform purpuric/necrotic vascular lesions, acute urticarial lesions, and vesicular/varicella‐like lesions A multi‐system inflammatory syndrome in children akin to Kawasaki syndrome has been described What does this study add? To our knowledge, this is the first description of classic Bullous Pemphigoid evolving from vesicular lesions caused by prolonged SARS‐Cov2 induced skin inflammation